Flexural Behavior of Reinforced Concrete Beams Reinforced with Glass Fiber Reinforced Polymer Rectangular Tubes - Yuan, Jian S.; Gao, Danying; Zhu, Haitang; Chen, Gang; Zhao, Liangping (Frontiers in Materials, 2020)
Glass fiber reinforced polymer (GFRP) pultruded rectangular tubes were used externally to confine Reinforced Concrete (RC) beams in this experimental study, aiming to improve the corrosion resistance of the RC beams in the harsh environment (e.g. Hydraulic structures and Marine structures). The flexural behaviour of the composite beams reinforced with GFRP tubes was investigated by using four-point bending test. The experimental program involved the testing of six beam specimens reinforced with or without the GFRP tubes, and the main parameters investigated included the reinforcement ratio of the tensile steel bars and the stirrup spacing. The experimental results show that the flexural strength and stiffness of the RC beam members were significantly improved by using the GFRP tubes. The brittle failure of the beam specimens was caused by the local failure at one loading pints on the top flange of the GFRP tubes. The higher reinforcement ratio of the tensile steel bars contributed to the improvement of the flexural strength and bending stiffness. The stirrup spacing had little effect on the flexural behaviour of the beam specimens in the proposed composite beams.